A STUDY TO DETERMINE THE PURCHASING INTENTION OF USA ORIGIN PRODUCTS DUE TO CONSUMER ANIMOSITY OF TURKISH CONSUMERS (Third Sector Social Economic Review, 2021)
Reasons sourced from the political and economic tensions between Turkey and the United States Turkish consumers of US origin products to be perspective and in this study to determine the intention of buying consumers with face to face interviews method of consumer animosity scale and product judgemenet scale questions were asked. The population of the study consists of consumers living in Ankara, and because of the size of the universe, a sample of research has been chosen with easy sampling.286 of the questionnaire studies applied to approximately 324 people were considered valid and subjected to relevant analysis. Turkey - also a way to tension from time to time and watch USA relations, Turkey and continues its activities as an intensive USA trade. In this study, which was carried out to determine the point of view of Turkish consumers towards this situation, it was observed that consumers developed an average level of consumer animosity towards USA products and that the positive view of the products belonging to this country was average, but the intention to purchase technological products in USA products was the most prominent product group in the category. The reason for this can be said that the USA has superiority skills in this regard.
Keywords: Consumer Animosity; Product Origin; Product Judgement; Turkey-USA